Harmony: psychological meaning today in reference to origins and context in the culture of the Middle Ages. - Drzewiecki, Bartosz (Studia Psychologica: Theoria et praxis, 2006)
Harmony is an exceptional mental state in human.s life and existential condition as well. As a scientific notion, "harmony" is used not very often, probably because of troubles with detailed description of this expression. Present article is a probe of concise presentation for fundamental meanings of notion "harmony" in contemporary psychology. Afterwards I would like to present roots and connections with the culture from .the harmony. has pervaded to our times. The Middle Ages. As an especially important elements in history of this noumenon, author mentions the connections with aesthetics, arts and music from has pervaded to the world of science in the times when neither aesthetics nor psychology exists as distinct of science. So author tries to approach meaning, sphere and history of the "harmony".